PENGARUH PERPUTARAN MODAL KERJA, KEBIJAKAN DEVIDEN DAN RASIO HUTANG TERHADAP NILAI PERUSAHAANDENGAN PROFITABILITAS SEBAGAI VARIABELINTERVENING - Carolina, Debi (Universitas muhammadiyah palembang, 2017)
This study discusses the effect of working capital turnover, dividend policyand debt ratio to the value of the company to profitability as an interveningvariable (study on property and real estate companies listed on the IndonesiaStock Exchange) periode 2010-2015. The independent variable used wasworking capital turnover, dividen policy, debt ratio, profitability (return onequity) as intervening variable and dependent variable was the value ofcompany (price earning ratio). The sampling method use was purposivesampling with a sample of 8 companies. Data collection techniques wasdocumentation technique. The analysis methods of this study used theclassical assumption test and path analysis test.From the research that has been done, it can be seen that there was asignificant effect of working capital turnover, and debt ratio of debt as partiallyto profitability, and there was no significant effect of dividend policy aspartially to profitability. There was simultaneous effectf working capitalturnover, dividend policy, and debt ratio to profitability. There was significanteffect of working capital turnover as partially to the value of company, andthere was no significant effect of debt ratio and profitability as partially to thevalue of company. And There was simultaneously effect of working capitalturnover, debt ratio and profitability to the value on property and real estatecompanies listed on Indonesia Stock Exchange. Profitability couldn’t beintervening for independent variable to the value of company. The mostdominant factor affected the value of the company at property and real estatecompanies listed on the Indonesia Stock Exchange is working capitalturnover.